The Origin of Dust Polarization in the Orion Bar - Le Gouellec, Valentin J. M.; Andersson, B-G; Soam, Archana; Schirmer, Thiébaut; Michail, Joseph M.; Lopez-Rodriguez, Enrique; Flores, Sophia; Chuss, David T.; Vaillancourt, John E.; Hoang, Thiem; Lazarian, Alex (The Astrophysical journal, 2023)
The linear polarization of thermal dust emission provides a powerful tool to probe interstellar and circumstellar magnetic fields, because aspherical grains tend to align themselves with magnetic field lines. While the Radiative Alignment Torque (RAT) mechanism provides a theoretical framework for this phenomenon, some aspects of this alignment mechanism still need to be quantitatively tested. One such aspect is the possibility that the reference alignment direction changes from the magnetic field (“ B -RAT”) to the radiation field k-vector (“ k -RAT”) in areas of strong radiation fields. We investigate this transition toward the Orion Bar PDR, using multiwavelength SOFIA HAWC+ dust polarization observations. The polarization angle maps show that the radiation field direction is on average not the preferred grain alignment axis. We constrain the grain sizes for which the transition from B -RAT to k -RAT occurs in the Orion Bar (grains ≥ 0.1 μ m toward the most irradiated locations), and explore the radiatively driven rotational disruption that may take place in the high-radiation environment of the Bar for large grains. While the grains susceptible to rotational disruption should be in suprathermal rotation and aligned with the magnetic field, k -RAT aligned grains would rotate at thermal velocities. We find that the grain size at which the alignment shifts from B -RAT to k -RAT corresponds to grains too large to survive the rotational disruption. Therefore, we expect a large fraction of grains to be aligned at suprathermal rotation with the magnetic field, and to potentially be subject to rotational disruption, depending on their tensile strength.